A metallurgical and thermal analysis of Inconel 625 electron-beam welded joints (Fracture and Structural Integrity, 2019)
Inconel 625 is a nickel-based superalloy that finds application in many industrial sectors thanks to its high strength, excellent fabricability, and  outstanding corrosion resistance. It is characterized by a good weldability and often used in the as-welded conditions. In the following, a metallurgical and thermal analysis of Inconel 625 Electron-Beam welded joints is described. The thermal analysis was supported by a numerical model that uses a superimposition of a spherical and a conical shape heat source with Gaussian power density distribution in order to reproduce the nail-shape of the fusion zone. The heat source parameters were calibrated by using experimental data coming from metallurgical observations and temperature measurements. Numerical and experimental results were found in good agreement.
Keywords: Welding; Inconel 625; Thermal Analysis; Numerical Modelling; Microstructure